Institutional personas – Dis/harmonic representations of higher music education - Moberg, Nadia; Georgii-Hemming, Eva (Högre utbildning, 2021)
Self-promotion and the role of ‘brand image’ have increased in importance within higher education. Drawing on multimodal material from websites, this paper deals with how institutions for higher music education discursively construct institutional personas. Higher music education represents a novel case that contributes to existing knowledge of how institutions represent themselves because it sits at a particular, unique juncture between perspectives on universities as places for education and places for training. By investigating representations – and the actors, beliefs and customs these include – our results shed light on institutional ideals concerning knowledge and education. In conclusion, the institutional personas are explained as dis/harmonic as fundamental contradictions with educational implications are revealed.